Canagliflozin for the treatment of adults with Type 2 diabetes. (May 2015) - Meininger, Gary; Canovatchel, William; Polidori, David; Rosenthal, Norm
SUMMARY : Canagliflozin is an SGLT2 inhibitor approved for the treatment of adults with Type 2 diabetes mellitus (T2DM). A comprehensive Phase III program evaluated canagliflozin in a broad range of patients with T2DM on various background therapies; studies were also conducted in special populations, including older patients and those with moderate renal impairment. Canagliflozin provided clinically meaningful reductions in HbA1c, bodyweight and blood pressure versus placebo and active comparators in studies up to 104 weeks. Canagliflozin was generally well tolerated, with increased incidences of adverse events related to the mechanism of action, including genital mycotic infections and osmotic diuresis-related adverse events. Overall, canagliflozin appears to be a useful treatment option for patients with inadequately controlled T2DM.